2009
DOI: 10.1371/journal.pone.0007835
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Seven Years of Phase III Trials for Patients with Extensive Disease Small-Cell Lung Cancer: Disappointing Results

Abstract: BackgroundFew studies have formally assessed whether treatment outcomes have improved substantially over the years for patients with extensive disease small-cell lung cancer (ED-SCLC) enrolled in phase III trials. The objective of the current investigation was to determine the time trends in outcomes for the patients in those trials.Methods and FindingsWe searched for trials that were reported between January 1981 and August 2008. Phase III randomized controlled trials were eligible if they compared first-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 23 publications
1
73
0
1
Order By: Relevance
“…Cells (25,,000 cells/well) were seeded in a 96-well microtiter plate and cultured overnight. The next day, PF-4989216 was added to each well starting at 10 mmol/L with a 3-fold serial dilution for 2 hours.…”
Section: Translational Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Cells (25,,000 cells/well) were seeded in a 96-well microtiter plate and cultured overnight. The next day, PF-4989216 was added to each well starting at 10 mmol/L with a 3-fold serial dilution for 2 hours.…”
Section: Translational Relevancementioning
confidence: 99%
“…Response to second-line chemotherapy for patients with refractory disease is less than 10%, and survival is 3 to 4 months (22,23). Multiple phase III trials have been conducted; however, the survival of patients with SCLC has not improved significantly over the years (24,25). Therefore, a targeted therapeutic approach is in strong demand for patients with SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…SCLC is a highly aggressive and nearly universally lethal cancer, for which few tractable therapeutic targets have been identified. Many large-scale clinical trials, conducted without biomarker selection, have failed to advance the standard of care for this disease (42,43). Carefully defined biomarkers that would focus novel therapeutic studies on the potentially responsive subset of patients could change this field.…”
Section: Genome-wide Loss-of-function Screens Identify Antxr1 As Essementioning
confidence: 99%
“…Small cell lung cancer is initially very responsive to chemotherapy; however, most patients relapse and die within 2 years (17). A recent review of nearly three decades of small cell lung cancer phase III clinical trials for extensive disease involving over 10,000 patients found no significant improvement in patient survival times over that period of time (23).…”
Section: Introductionmentioning
confidence: 99%